UPAYA GURU DALAM MEMBENTUK KARAKTER DISIPLIN SISWA DI SEKOLAH DASAR - Vitalis Tarsan; Hermanus Saman; Arnoldus Helmon; Vinsensius Sumardi (Jurnal Literasi Pendidikan Dasar (JLPD), 2022)
Everyone would agree that upholding discipline is important. In fact, many students are undisciplined. Discipline is not an innate trait. It must be fought for, trained and accustomed. School is one of the formal institutions that are obliged to train and get used to a disciplined life. T eacher is one component in schools that play a strategic role in training and getting used to disciplined life. This essay proposes several theoretical-solution concepts about teacher strategies in training and teaching students to live disciplined lives. As for the focus of the study, the teacher's strategy, in this article: teaches, familiarizes, guides, sets an example, enforces rules, gives punishment and sanctions, and conducts monitoring and evaluation.